Evidence of efficacy of the Integrated Literacy Study Group professional learning program to enhance reading instruction for students with emotional and behavioral disorders. Issue 1 (13th July 2022) - Benner, Gregory J.; Filderman, Marissa J.; Barnard‐Brak, Lucy; Pennefather, Jordan; Smith, Jean Louise M.; Strycker, Lisa A.
Abstract: This article reports on a pilot study of the Integrated Literacy Study Group, a digitally delivered professional learning intervention to prepare elementary school teachers to provide evidence‐based reading instruction and behavioral strategies to students with or are at risk for emotional and behavioral disorders. Using broadcast methods, we recruited 72 teachers across five states in the western United States to participate in the randomized controlled trial. Intervention teachers, relative to controls, made significant gains in self‐efficacy and use of the reading and behavioral strategies learned in the professional learning program. Students with or at risk of emotional and behavioral disorders served by participating teachers made significant improvements in academic competence and engagement. Teacher professional learning can improve teacher knowledge of evidence‐based reading and behavioral strategies for students with (or at risk for) emotional and behavioral disorders, teacher self‐efficacy, and teacher practice, with positive impacts on student early literacy and academic competence. Abstract : Teacher professional development improves outcomes for educators and students. Practitioner Points: 1. Elementary teachers are challenged by students with or at risk for emotional and behavioral disorders. 2. An online intervention helped teachers manage student behavior and improve reading instruction. 3. Teachers improved self‐efficacy and students gained academic competence.